Nursing students' attitudes towards provision of sexual health care in clinical practice. Issue 23 (8th May 2013) - Huang, Cheng‐Yi; Tsai, Li‐Ya; Tseng, Tsui‐Hwa; Li, Chi‐Rong; Lee, Sheuan
Abstract : Aims and objectives: To investigate nursing students' attitudes towards providing sexual health care in clinical practice and to identify associated factors. Background: Sexual health care is an important component of holistic health care. Nurses' personal sexual knowledge and attitudes are shown to influence provision of sexual health care. Design: This is a descriptive, cross‐sectional study. Methods: We selected 146 senior nursing students by convenience sampling from nursing schools in two medical universities in central Taiwan. Data were collected using the Nursing Attitudes on Sexual Health Care scale developed based on the 'Permission/Limited Information/Specific Suggestions/Intensive Therapy' model. Higher scores indicated more positive attitudes. Results: Participants' mean age was 22·15 years. Mean total Nursing Attitudes on Sexual Health Care scores ranged from 45–75 (61·40 ± 10·17). Nursing students' most positive attitudes towards Permission/Limited Information/Specific Suggestions/Intensive Therapy sexual healthcare interventions were at the Permission level, and least positive attitudes were at levels of Specific Suggestion and Intensive Therapy. The top three positive items were as follows: accept patients' expression of sexual concerns, initiate discussions and encourage patients to talk. Male nursing students had negative attitudes towards sexual healthcare interventions, which became more positive as age increased, especially at the Limited Information level. Conclusions: Nursing students had different attitudes towards different levels of sexual health care in the Permission/Limited Information/Specific Suggestions/Intensive Therapy model. Attitudes were associated with age and gender. The Nursing Attitudes on Sexual Health Care scale is useful and reliable for identifying nurses' attitudes towards providing sexual health care. Relevance to clinical practice: The Permission/Limited Information/Specific Suggestions/Intensive Therapy‐based Nursing Attitudes on Sexual Health Care scale helps to identify nurses' attitudes. A better understanding of nurses' attitudes towards provisional sexual health care will provide information needed to develop appropriate education programmes to improve delivery of sexual health care.